Radiopaque UHMWPE sublaminar cables for spinal deformity correction: Preclinical mechanical and radiopacifier leaching assessment. Issue 2 (27th March 2017) - Roth, Alex K.; Boon‐Ceelen, Karlien; Smelt, Harold; van Rietbergen, Bert; Willems, Paul C.; van Rhijn, Lodewijk W.; Arts, Jacobus J.
Abstract: Polymeric sublaminar cables have a number of advantages over metal cables in the field of spinal deformity surgery, with decreased risk of neurological injury and potential for higher correction forces as the two most predominant. However, currently available polymer cables are radiolucent, precluding postoperative radiological assessment of instrumentation stability and integrity. This study provides a preclinical assessment of a woven UHMWPE cable made with radiopaque UHMWPE fibers. Our primary goal was to determine if the addition of a radiopacifier negatively affects the mechanical properties of UHMWPE woven cables. Tensile mechanical properties were determined and compared to suitable controls. Radiopacity was evaluated and radiopacifier leaching was assessed in vitro and in vivo . Finally, in vivo bismuth organ content was quantified after a 24‐week implantation period in sheep. Results show that the mechanical properties of woven UHMWPE cables were not deleteriously affected by the addition of homogenously dispersed bismuth oxide particles within each fiber. Limited amounts of bismuth oxide were released in vitro, well below the toxicological threshold. Tissue concentrations lower than generally accepted therapeutic dosages for use against gastrointestinal disorders, well below toxic levels, were discovered in vivo . These results substantiate controlled clinical introduction of these radiopaque UHMWPE cables. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 771–779, 2018.